(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2013)
The study was aimed to observe reproductive pattern and efficiency of Red Chittagong Cattle (RCC) including reproductive history taken from two different herds; nucleus herd (on-station) and community herd (on-farm) in Mymensingh district of Bangladesh. A total of 184 calving parity records from 66 RCC cows that included 317 estrous, 164 conception and 178 calving history covering a period from 2005 to 2011 were considered for analyses. The highest frequencies of estrous, conception and calving occurred in May (13%, 15% and 14%, respectively), while the lowest in September for estrous (4%) and conception (4%) and April and June for calving (5%). The month of the year had significant (p<0.001 to p<0.05) effect on both estrous and calving but not for conception (p>0.05). There was no significant effect of season with estrous or conception or calving, but numerically highest incidence of estrous and conception in summer (36% and 38%, respectively) and calving in winter (36%) are noted. The seasonal indexes of calving in the on-station and on-farm herds were 0.73 and 0.78 respectively, with an overall mean of 0.68. The breeding or reproductive efficiency of the nucleus herd was estimated based on calving interval and age at first calving along with calving interval and the calculated results were 79 % and 82%, respectively for those two methods of estimation. The result obtained in this study indicates the reproductive behavior of RCC did not differ significantly by season, but varied with month of the year. In addition, reproductive efficiency of RCC in this study was slightly lower than that of expected.